Tetraacylstannanes as Long‐Wavelength Visible‐Light Photoinitiators with Intriguing Low Toxicity. Issue 33 (29th May 2018) - Radebner, Judith; Eibel, Anna; Leypold, Mario; Jungwirth, Nina; Pickl, Thomas; Torvisco, Ana; Fischer, Roland; Fischer, Urs Karl; Moszner, Norbert; Gescheidt, Georg; Stueger, Harald; Haas, Michael
Abstract: The first tetraacylstannanes Sn[(CO)R]4 ( R =2, 4, 6‐trimethylphenyl (1 a ) and 2, 6‐dimethylphenyl (1 b )), a class of highly efficient Sn‐based photoinitiators, were synthesized. The formation of these derivatives was confirmed by NMR spectroscopy, mass spectrometry, and X‐ray crystallography. The UV/Vis absorption spectra of1 a,  b reveal a significant redshift of the longest wavelength absorption compared to the corresponding germanium compounds. In contrast to the known toxicity of organotin derivatives, the AMES test and cytotoxicity studies reveal intriguing low toxicity. The excellent performance of1 as photoinitiators is demonstrated by photobleaching (UV/Vis) and NMR/CIDNP investigations, as well as photo‐DSC studies. Abstract : Breaking borders : The first examples of tetra‐acylstannanes have been synthesized. Their outstanding potential as a unique class of long‐wavelength visible‐light photoinitiators (PIs) for free‐radical polymerization was demonstrated. Notably, low toxicity was found, which enables any application, when biocompatibility and costs are an issue (see figure).